Analysis of formation and balanced development of regional economic systems - A. A. Shatsky (Вестник университета, 2024)
The relevance of the study is conditioned by the fact that in recent years the level of regional socio-economic systems development has been significantly affected by various negative factors, and it is necessary to carry out an operational analysis that will help to identify them in a timely manner.   Uneven development of regions is characteristic of many countries and is determined by the peculiarities of historical traditions, current economic potential and interrelations with international communities, as well as by state regional policy. The level of innovative development and society digitalization creates conditions for the transition of Russia from a resource-based economy to an investment and innovation economy in order to improve and maintain competitiveness. As a result of the research and study of the scientists’ materials, who have investigated the ways and mechanisms of analyzing regional socio-economic systems formation and development, as well as their impact on the Russian economy development, which at the present stage is reaching a new level in the conditions of sanctions, we have conducted an assessment of regional socio-economic systems and various methods of its implementation.